Structural flexibility is a decisive factor in FLP dihydrogen cleavage with tetrahedral Lewis acids: a silane case study - Thorwart, Thaddäus; Greb, Lutz (Chemistry - a European journal, 2024)
Dihydrogen activation is the paradigmatic reaction of frustrated Lewis pairs (FLPs). While trigonal-planar Lewis acids have been well established in this transformation, tetrahedral Lewis acids are surprisingly limited. Indeed, several cases were computed as thermodynamically and kinetically feasible but exhibit puzzling discrepancies with experimental results. In the present study, a computational investigation of the factors influencing dihydrogen activation are considered by large ensemble sampling of encounter complexes, deformation energies and the activation strain model for a silicon/nitrogen FLP and compared with a boron/phosphorous FLP. The analysis adds the previously missing dimension of Lewis acids’ structural flexibility as a factor that influences preexponential terms beyond pure transition state energies. It sheds light on the origin of “overfrustration” (defined herein), indicates structural constraint in Lewis acids as a linchpin for activation of weak donor substrates, and allows drawing a more refined mechanistic picture of this emblematic reactivity.
Gesehen am 26.11.2024